113+-6x=53

Simple and best practice solution for 113+-6x=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 113+-6x=53 equation:



113+-6x=53
We move all terms to the left:
113+-6x-(53)=0
determiningTheFunctionDomain -6x+113-53+=0
We add all the numbers together, and all the variables
-6x=0
x=0/-6
x=0

See similar equations:

| x^2-17x+57=-15 | | 2^2-17x+57=-15 | | 8−2v=–5v−10 | | 8d+5=5+8d | | 20+5p=60 | | 1/5(3b+5)=28 | | 15(3b+5)=28 | | B+2b+2b+30=250 | | 16a2=9 | | 3^3^x=1/243 | | 32=3r+5r | | -36=X2+12x | | 3b+30=250 | | 35b=250 | | 34=9+5(d+4) | | 20x–60000/x^2=0 | | 9^x+4=27 | | 30+5b=250 | | 2+6n=2(n+9) | | 1/20=n/1000 | | 3^3x=1/243 | | B-1/2b=22 | | -1/2(-6x-5/20+1=9x | | 6(1+7y)=552 | | -7n+7(4-2n)=-24+5n | | (2n)18=(n+1)14 | | 3p-5+16=2p+3+20 | | -5(-2m-8)-3=1-8m | | 70=5(4s+6) | | 7z+28=63 | | 3(n+8)+8=40+3n | | 2-5/9v=23 |

Equations solver categories